The Relationship of Characteristics, Knowledge, Attitudes, and Mother’s Action on Immunization Compliance - Alfiyan Dharma Yuda; Ira Nurmala (Jurnal Berkala Epidemiologi, 2018)
Background: Immunization coverage in Indonesia in 2015 was 86,50%, which did not meet the target of complete primary immunization was 91%. The completion of primary immunization is defined by several factors such as characteristics, knowledge, attitude, and mother’s action. Purpose: This study was aimed to investigate the correlation between mother’s characteristics, knowledge, attitude, and action toward immunization compliance in community group (RW) 15 in Sub-district Semampir Surabaya City. Methods: The study was designed as a cross-sectional study with a guy sampling method. In this method, the respondents were selected from 10% of total population and obtained 78 respondents with criteria of a mother having a toddler around 1-5 years old, pregnant mother, and adult women of childbearing age. Primary data were collected from a questionnaire through the interview. Meanwhile, the secondary data were obtained from the public health center of Wonokusumo and public health office of Surabaya city. Data were analyzed through the chi-square method. Results: The bivariate statistical analysis showed that there is a relation between mother’s characteristic (age, education, and employment) (p = 0,01), knowledge (p = 0,01), attitude (p = 0,01), and action (p = 0,01) with immunization compliance. Conclusion: It can be concluded that mother’s characteristic, knowledge, attitude, and action can be determining the factor of immunization compliance.